Transcriptome Analysis of the Hippocampus in Domestic Laying Hens with Different Fear Responses to the Tonic Immobility Test - Jingyi Zhang; Min Li; Liying Pan; Ye Wang; Hui Yuan; Zhiwei Zhang; Chaochao Luo; Runxiang Zhang (Animals)
Fear is a critical welfare concern in laying hens. Fearful behaviors in domestic chickens are influenced by both genetic and environmental factors, contributing to individual differences in stress responses. Tonic immobility (TI) duration is widely recognized as a reliable indicator of fear levels. The hippocampus, a critical brain region for emotional states, plays a pivotal role in associating fearful experiences with specific stimuli, enabling adaptive behavioral responses. This study investigated hippocampal histological characteristics and transcriptomic profiles in laying hens with different fear responses categorized based on TI duration. A total of 80 native Lindian hens (75 weeks old) were individually housed in modified conventional cages. At 76 weeks of age, hens exhibiting the longest and shortest TI durations were classified into the high-fear (TH) and low-fear (TL) groups, respectively. Whole hemibrains were collected for histological and immunohistochemical analyses, while hippocampal tissues underwent transcriptome sequencing. The results showed a significant reduction in Nissl body counts in hippocampal neurons of high-fear hens (p < 0.05), suggesting potential neuronal damage or functional impairment. Transcriptomic analysis revealed 365 differentially expressed genes (DEGs) between two groups, with 277 upregulated and 88 downregulated genes in TH chickens. KEGG pathway enrichment analysis identified seven significantly associated pathways (p < 0.01), including retinol metabolism, vitamin B6 metabolism, and nicotinate and nicotinamide metabolism, all of which are crucial for neuronal function and immune regulation. In addition, a significant increase in DCX protein expression (p < 0.05) and a decrease in c-Fos protein expression (p < 0.05) was noted in in high-fear hens, whereas PCNA levels remained unchanged (p > 0.05) under immunohistochemical validation. The neuronal alterations observed in high fear individuals suggest neural damage, while transcriptomic variations point to potential disruptions in neurogenesis, synaptic signaling, and stress-related pathways. Collectively, these results provide novel insights into the neurobiological basis of fear regulation in laying hens and may have implications for poultry welfare and management strategies.